Prevalence of pain awareness, treatment, and associated health outcomes across different conditions in Brazil - Amir Goren; Hillary Johanna Gross; Ronaldo Kenzou Fujii; Abhishek Pandey; Joaquín Mould-Quevedo (Revista Dor)
BACKGROUND AND OBJECTIVES: Pain is a prevalent clinical condition causing tremendous humanistic and economic burden worldwide. With limited research into the impact of pain on health related outcomes in Brazil, the current study examined prevalence of pain conditions, rate of diagnosis and treatment, and potential impact on health outcomes among Brazilian adults. METHOD: Data were collected from the stratified random sample of adults (n = 12,000) in thecross-sectional 2011 National Health and Wellness Survey (NHWS) in Brazil. Respondents reported on sociodemographic information, health-related quality of life (SF-12v2), work productivity and activity impairment (WPAI), comorbid conditions, and healthcare resource use. Comparisons between those reporting pain and no pain (i.e.,neuropathic pain, fibromyalgia, surgery/medical procedure-related pain, or back pain, versus controls without the respective condition; or arthritis, with vs. without experiencing pain) were conducted using Chi-square and t-tests for categorical and continuous variables, respectively. RESULTS: Back pain was the most commonly reported pain condition (12%), followed by fibromyalgia. Among those experiencing the condition neuropathic pain was the most, and back pain the least, commonly diagnosed and treated. Across conditions, to varying degrees, pain vs. no pain was associated with greater comorbid burden, higher resource utilization, and greater impairments in health status and work productivity, with few differences in sociodemographic factors. CONCLUSION: Pain-related conditions were associated with varying awareness and treatment rates among Brazilian adults. Consistent with previous US and European studies, pain was associated with various negative health outcomes. These findings highlight the under-treatment and range of potential sources of pain burden in Brazil.